Religiousness Attitude During Adulthood Elderly (Psychology Of Religion Perspectives) - Subhi, Muhamad Rifa'i (IAIN Pekalongan, 2017)
Islam teaches the difference in someone's level of religiosity. The level of human religiosity can change from one moment to another. Humans have evolved a religious life. Including human experience in adulthood elderly in life and face the problems of life. This study focused on the real description of the attitude of religiosity which is owned by the elderly. The study was taken from the students at the boarding school Elderly Islamic boarding school (Pesantren) of Roudlotul Muta'allimin Dracik Kramat Batang. The research method used descriptive qualitative approach to straight dialogue (interview) of the respondents, namely the students of Elderly Islamic Boarding School (Pesantren). The study results showed that each of the students have the different religious involvement in filling elderly period (retirement). The involvement includes Ritual Involvement, Ideological Involvement, Intellectual involvement, experimental involvement, and consequential involvement.